2005
DOI: 10.1111/j.1365-3164.2005.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the group 1 Dermatophagoides allergens Der p 1 and Der f 1 in homes with no dogs, healthy dogs and Dermatophagoides‐sensitized atopic dogs in Liverpool

Abstract: Dermatophagoides farinae is a frequent allergen in canine atopic dermatitis despite its reported scarcity in the UK, and the aim of this study was to determine whether dogs were uniquely exposed to this species. Der f 1 and Der p 1 in dust collected from living room carpets, bedroom carpets and dog beds of 13 houses with no dogs, 13 with healthy dogs, and 16 with Dermatophagoides-sensitized atopic dogs were quantified by ELISA. Der p 1 levels (microg g(-1) house dust) were significantly higher than Der f 1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
48
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 43 publications
8
48
2
2
Order By: Relevance
“…This suggests that the presence of pets in homes may, for some reason, have resulted in both lower mite densities and reduced Der p 1 allergen levels in the home. A similar observation was reported in a study conducted in Liverpool (Raffan et al , ), which suggests that more frequent cleaning and vacuuming may be carried out by dog owners as a result of excess build‐up of skin and hair shedding around the home, inadvertently reducing mite densities in the process. This also seems to be reflected in the questionnaire data from bedrooms in this study.…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that the presence of pets in homes may, for some reason, have resulted in both lower mite densities and reduced Der p 1 allergen levels in the home. A similar observation was reported in a study conducted in Liverpool (Raffan et al , ), which suggests that more frequent cleaning and vacuuming may be carried out by dog owners as a result of excess build‐up of skin and hair shedding around the home, inadvertently reducing mite densities in the process. This also seems to be reflected in the questionnaire data from bedrooms in this study.…”
Section: Discussionsupporting
confidence: 79%
“…This could explain the positive reactions to D. farinae in dogs from areas with low levels of Der f 1, although other hypotheses have been proposed, e.g. cross-reactions with D. pteronyssinus (Raffan et al, 2005) or other mites (Noli, 1998) (Noli, 1998) or lower allergenicity of D. pteronyssinus to dogs compared with D. farinae (Schumann et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in Liverpool (UK) showed that Der f 1 levels were generally 100-1000 times lower than Der p 1 levels (Raffan et al, 2005). Similarly, in Galicia, D. pteronyssinus is the predominant house dust mite since Der f 1 levels are very low or undetectable (Boquete et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitisation to house dust mite and moulds account for the majority of sensitisations in dogs with atopic eczema/atopic dermatitis and illustrates the similarity of reaction patterns to environmental influences in humans and animals with respect to allergies (Zur et al, 2002). Concerning house dust mite allergens it is assumed that in dogs D. farinae plays a more important role than D. pteronyssinus (Mueller et al, 2000;Nuttall et al, 2006;Tarpataki et al, 2006), although the prevalence of the Der f1 allergen was found to be rather low in households from the UK (Raffan et al, 2005). Environmental influences including allergen and (air) pollutant exposure such as tobacco smoke may be shared by humans and their pets and contribute to the manifestation of allergies in both species.…”
Section: Discussionmentioning
confidence: 99%